2021
DOI: 10.11607/ijp.6735
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Internal Accuracy and Load-Bearing Capacity of Minimally Invasive Lithium Disilicate Occlusal Veneers

Abstract: Purpose: To test whether internal accuracy affects the load-bearing capacity of 0.5-mm-thick occlusal veneers made out of milled or heat-pressed lithium disilicate (LS2). Materials and methods: Extracted human molars (N = 80) were divided into four groups (n = 20 each) depending on the bonding substrate (enamel [E] or dentin [D]) and the fabrication method (milling [CAD] or heat pressing [PRE]) for the occlusal LS2 veneers: (1) E-CAD, (2) D-CAD, (3) E-PRE, or (4) D-PRE. After restoration fabrication, the abutm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 30 publications
(48 reference statements)
0
15
0
1
Order By: Relevance
“…An article reviewing preclinical studies concerning CAD/CAM occlusal veneers suggests 0.7–1.0 mm of thickness to be appropriate for LDS occlusal veneers 23 . It was additionally shown that good internal accuracy of LDS occlusal veneers increased their failure load 8 with a superior performance of pressed restorations 29 …”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…An article reviewing preclinical studies concerning CAD/CAM occlusal veneers suggests 0.7–1.0 mm of thickness to be appropriate for LDS occlusal veneers 23 . It was additionally shown that good internal accuracy of LDS occlusal veneers increased their failure load 8 with a superior performance of pressed restorations 29 …”
Section: Discussionmentioning
confidence: 99%
“…7 An article reviewing preclinical studies concerning CAD/CAM occlusal veneers suggests 0.7-1.0 mm of thickness to be appropriate for LDS occlusal veneers. 23 It was additionally shown that good internal accuracy of LDS occlusal veneers increased their failure load 8 with a superior performance of pressed restorations. 29 However, preclinical data on premolar restorations is scarce and mostly focuses on occlusal onlays not covering the labial aspect 6,10 or describe labial veneers without covering the occlusal surface.…”
Section: Failure Analysis After Slfmentioning
confidence: 99%
See 3 more Smart Citations